2016
DOI: 10.5365/wpsar.2016.7.2.012
|View full text |Cite
|
Sign up to set email alerts
|

A Q fever cluster among workers at an abattoir in south-western Sydney, Australia, 2015

Abstract: BackgroundIn September 2015, the Public Health Unit of the South Western Sydney Local Health District was notified of two possible Q fever cases. Case investigation identified that both cases were employed at an abattoir, and both cases advised that co-workers had experienced similar symptoms. Public Health Unit staff also recalled interviewing in late 2014 at least one other Q fever case who worked at the same abattoir. This prompted an outbreak investigation.MethodsThe investigation incorporated active case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…During 2013–2017, more than 2500 cases of Q fever were notified in Australia; studies have found that in 40–50% of notified cases patients were hospitalised for a median 4–6 days . A recent death linked to Q fever underscores the importance of preventing this infection …”
mentioning
confidence: 99%
“…During 2013–2017, more than 2500 cases of Q fever were notified in Australia; studies have found that in 40–50% of notified cases patients were hospitalised for a median 4–6 days . A recent death linked to Q fever underscores the importance of preventing this infection …”
mentioning
confidence: 99%
“…Considering the highly resistant nature of the bacterium and repeated reports on isolation of the microorganism from soil after six months removal of an infected animal, frequent shedding of the microorganism in the milk of infected animals and difficulties in identification of the disease in a routine meat inspection program make it essential to pay more attention to the disease as a neglected zoonotic disease [29]. In a report recently published by World Health Organization, an aggregate presence of Q fever in an Australian abattoir has also confirmed the importance of this zoonotic disease as a neglected occupational hazard to the slaughterhouse workers and to set a preventive program by using a potent vaccine [6].…”
Section: Resultsmentioning
confidence: 98%
“…The main causative agent of Q fever, C. burnetii, is an obligate intracellular Gram-negative bacterium which may infect a variety rang of vertebrate and invertebrate populations and is also assumed as a biological terrorist organism [2][3][4]. The reports have implied that farm animals including cattle, sheep, and goats, play a major role as reservoir of the infection, with high risk to the vulnerable populations including ranchers, veterinarian, butchers and personnel of slaughterhouses [5][6][7]. Transmission routes of the infection to human are including infected ticks, aerosols, direct contact with the infected animal fluids such as milk, urine, seminal fluid, contaminated tissues such as kidneys, mammary glands and lymph nodes [2,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This is possible because a recent small study showed that only 25% (2/8) of Q fever cases from one abattoir had previously received Q fever vaccination (Lord et al 2016). The immune status (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an investigation of Q fever cluster among workers at an abattoir in South-Western Sydney, Australia, 2015, reported that the majority (75%) of employees were not vaccinated against Q fever despite the high-risk setting (Lord et al 2016). Further field investigation revealed that management and staff lacked knowledge and awareness of Q fever (Lord et al 2016).…”
Section: Discussionmentioning
confidence: 99%